Nickel (II) phthalocyanine-tetrasulfonic-Au nanoparticles nanocomposite film for tartrazine electrochemical sensing - de Lima, Lucas F.; Maciel, Cristiane C. [UNESP]; Ferreira, André L.; de Almeida, Jéssica C. [UNESP]; Ferreira, Marystela (Elsevier, 2020)
In this work, we report the analytical detection of tartrazine through differential pulse voltammetry (DPV) using gold nanoparticles (AuNPs) and Nickel(II)-phthalocyanine-tetrasulfonic (NiTsPc). The Layer-by-Layer (LbL) film was constructed following the Au-(AuNPs-PAH/NiTsPc)5 architecture. The electric current characteristics of this sensor were verified by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). As a result of these measurements, a large and well-defined redox peak was obtained, indicating a significant enhancement in electron transfer. Excellent sensing performance was achieved with high sensitivity (25.79 ± 0.47 (µA cm−2) (µmol L−1)−1 and 8.80 ± 0.36 (µA cm−2) (µmol L−1)−1), low limit of detection (0.055 µmol L−1 and 0.122 µmol L−1), and excellent anti-interference and repeatability behavior. The Au electrode modified with the LbL film was also evaluated in commercially available juice samples with a recovery range from 97.74% to 108.26%.
Keywords: Electrochemical detection; Gold-nanoparticles; LbL film; Nickel-(II)-phthalocyanine-tetrasulfonic; Tartrazine